Biochemical Profile of Chronic Kidney Disease (CKD) Patients in Various Age and Gender Group Subjects Visiting Kist Medical College & Teaching Hospital, Kathmandu - Paudel, YP; Dahal, S; Acharya, T; Joshi, AP; Shrestha, B; Khanal, M; Kafle, D (Journal of Chitwan Medical College, 2013)
Nowadays it is observed that the chronic kidney disease (CKD) is a growing health problem worldwide and the most common illness associated with this is hypertension (HTN) and diabetes mellitus (DM). This study tries to find out illness associated with CKD and assess the renal parameters according to age and sex group. This is a cross sectional descriptive study. Diagnosed cases of Chronic Kidney Disease patients visiting at KIST Medical College from September to November 2011 are included in this study. SPSS-17 version is used for data analysis and appropriate statistical tests are done. Among 150 patients, 57% are male and 43% are female. Mean age of the study population is 48.62±18.09 years. Level of urine protein for male is higher than female. Mean urea, creatinine, potassium, uric acid, phosphorus and protein creatinine ratio (PCR) are higher in younger age group. The result also depicts hypertension is the leading illness associated with CKD (50%). Only 8% diabetes mellitus cases are associated with CKD followed by both of hypertension and diabetes mellitus (26%) and 16% others. This study provides an overview of routine biochemical parameters with CKD. Hypertension is found as leading illness associated with CKD. Differences in renal parameters are found in gender and different age groups. DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8441 Journal of Chitwan Medical College Vol.3(2) 2013 36-39